2006
DOI: 10.1051/0004-6361:20065888
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of flare-CME productive active regions and CME speed

Abstract: Aims. We study the properties of magnetic field of flare-coronal-mass-ejection (flare-CME) productive active regions and their statistic correlations with CME speed. Methods. We used a sample of 86 flare-CMEs in 55 solar active regions. Four measures, including the tilt angle (Tilt), total flux (Ft), length of the strong-field and strong-gradient main neutral line (Lsg) and effective distance (d E ), are used to quantify the properties of the magnetic field of flare-CME productive active regions. (4) The occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…This parameter could roughly quantify the magnetic complexity of active regions. Our previous (Guo et al 2006, 2007; Guo & Zhang 2007) studies have confirmed that the higher d E , the more complex the magnetic field of the ARs. In the same way as in the previous work, we choose a threshold of 100 G to measure d E for the ARs from MDI synoptic charts.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…This parameter could roughly quantify the magnetic complexity of active regions. Our previous (Guo et al 2006, 2007; Guo & Zhang 2007) studies have confirmed that the higher d E , the more complex the magnetic field of the ARs. In the same way as in the previous work, we choose a threshold of 100 G to measure d E for the ARs from MDI synoptic charts.…”
Section: Methodssupporting
confidence: 59%
“…It has been pointed out that this parameter could describe the degree of isolation or mutual penetration of the two polarities of an AR quantitatively. Recently, using the Solar and Heliospheric Observatory (SOHO) Michelson Doppler Imager (MDI) line‐of sight magnetograms, we have carried out a systemic investigation of the quantitative study of the magnetic complexity of ARs with this parameter (named effective distance, d E , in our work: Guo & Zhang 2007; Guo, Zhang & Chumak 2007). We have carried out a statistical analysis with a large sample of 848 ARs and confirmed the basic agreement between the value of d E and MWMC.…”
Section: Introductionmentioning
confidence: 99%
“…Through examining 117 ARs, Canfield et al [1999] found that ARs are more likely to be eruptive if they are either sigmoidal or large. Guo et al [2007] investigated 55 flare‐CME productive ARs and found that fast CMEs tended to initiate in ARs with large magnetic flux or long lengths of main polarity inversion lines (PILs). Through investigating 57 fastest CMEs with speed larger than 1500 km s −1 from 1996 June to 2007 January as well as 1143 ARs recognized from magnetic synoptic charts obtained by Michelson Doppler Imager (MDI) on board Solar and Heliospheric Observatory (SOHO), Wang and Zhang [2008] found that there was a general trend that a larger, stronger, and more complex AR was more likely to produce a faster CME.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical studies show that there are close relationships between CMEs and active regions (ARs, Subramanian & Dere, 20 Zhou et al, 19 Guo et al, 21,22 Chen et al 23 ) and AR magnetic non-potentiality (Falconer et al, 24 Schmieder 25 ). However, the related-ARs do little effects on the kinematic properties of CMEs, except for the CME productivity (Chen et al 23 ).…”
Section: Cme-related Surface Activitymentioning
confidence: 99%
“…The eruption processes of flares/CMEs are well studied by many authors (e. g., Zhang et al, 26 Lin, 27 Guo et al, 22 and Wang & Zhang 28 ). In Zhou et al, 19 it is found that all the earth-directed halo CMEs were accompanied by the local brightening in EUV and/or Ha wavebands.…”
Section: Cme-related Surface Activitymentioning
confidence: 99%